2017
DOI: 10.1007/s00508-017-1216-9
|View full text |Cite
|
Sign up to set email alerts
|

Media use, sports activities, and motor fitness in childhood and adolescence

Abstract: Media use is an important determinant of juvenile sports activity and motor performance, being part of a complex juvenile leisure behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 33 publications
3
28
0
4
Order By: Relevance
“…The proportion of children with migration background in this longitudinal study (26%) is well in accordance with cross‐sectional studies by Greier and Riechelmann among Tyrolean preschool children (25%), and by Ruedl et al among Tyrolean primary school children (26%) and well comparable with a recent cross‐sectional study by Kaiser‐Jovy et al among Tyrolean secondary school children (22%).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The proportion of children with migration background in this longitudinal study (26%) is well in accordance with cross‐sectional studies by Greier and Riechelmann among Tyrolean preschool children (25%), and by Ruedl et al among Tyrolean primary school children (26%) and well comparable with a recent cross‐sectional study by Kaiser‐Jovy et al among Tyrolean secondary school children (22%).…”
Section: Discussionsupporting
confidence: 92%
“…Recently, Kaiser‐Jovy et al found among a cohort of about 400 Austrian 10‐14 years old secondary school students a mean time of self‐reported media use (watching TV, surfing in the Internet, use of smartphone, playing computer etc) of 10.3 hours on a weekday and 12 hours on weekends. As Kaiser‐Jovy et al did not find a significant influence of hours of media use on sport activity, they concluded that a heavy media use is part of a complex juvenile leisure behavior and therefore rather a “time killer” with regard to sport activity and physical fitness. In general, physical fitness is subdivided into health‐related fitness (cardiorespiratory endurance, muscular endurance and strength, body composition, flexibility) and skill‐related fitness components (agility, balance, coordination, speed, power, reaction time) which can be tested by a single test item assessment (eg, “shuttle run” covering cardiovascular endurance) or by entire motor test batteries .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last several decades there have been significant changes in physical activity levels of children and adolescents, particularly in highly developed countries, leading to increasingly sedentary behavioral choices (Hills, King & Armstrong, 2007). Watching TV, playing computer games and surfing the internet have become popular leisure time behaviors Greier, Drenowatz, Ruedl, Lackner, Kroell & Feurstein-Zerlauth, 2018;Kaiser-Jovy, Scheu & Greier, 2017;Mathers, Canterford, Olds, Hesketh, Ridley & Wake, 2009). Accordingly, various studies have shown that a majority of youth are not meeting current physical activity guidelines of 60-minutes of moderateto-vigorous PA (Krug, Jekauc, Poethko-Müller, Woll & Schlaud, 2012;Reilly, Jackson, Montgomery, Kelly, Slater, Grant & Paton, 2004;WHO 2010).…”
Section: Introductionmentioning
confidence: 99%